Appropriation of Assets Corruption in Human Rights Perspective - Sahat Maruli Tua Situmeang (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine how law enforcement in cases of criminal acts of corruption is viewed from the perspective of human rights and to find out how the system of confiscation of assets by the state from the proceeds of criminal acts of corruption is viewed from the perspective of human rights. The research method used is normative juridical and by using a statutory approach. The results show that the seizure of assets by the state through a criminal law mechanism can be carried out if the court has handed down a decision that has permanent legal force, therefore it must be carried out carefully, because if the confiscation has nothing to do with the proceeds of a criminal act of corruption, it has the potential to violate human rights (HAM). Through this research, The author is of the view that the confiscation of assets in cases of criminal acts of corruption must be formulated from a theoretical, juridical, philosophical and practical perspective as a justification so that it can be applied both at the level of legislation and application policies. So that the potential for the seized assets will not exceed the amount of the corrupted assets.